Exploring the effectiveness of physical activity interventions in women with previous gestational diabetes: A systematic review of quantitative and qualitative studies - A.K. Buelo; A. Kirk; R.S. Lindsay; R.G. Jepson (Preventive Medicine Reports, 2019)
Women with previous Gestational Diabetes Mellitus (GDM) have seven times the risk of Type 2 diabetes later in life compared to women without GDM. Physical activity can reduce this risk and most women with previous GDM are not physically active. Aims: To explore: (1) effectiveness of physical activity interventions for women with previous GDM; (2) factors that women with previous GDM perceive influence their physical activity; (3) how these factors are addressed by the interventions. Methods: A systematic review of quantitative (aim 1) and qualitative (aim 2) studies with a mixed-methods synthesis (aim 3) was conducted in October 2017 following Cochrane methodology. Of 8101 articles identified, twenty-eight studies were included in total: 18 in Review 1 and 10 in Review 2. Results: Four interventions significantly increased physical activity and 14 had either mixed effectiveness or no changes in physical activity. Reporting of intervention components and study quality varied greatly. Relevant qualitative factors included accounting for childcare issues, social support and cultural sensitivities. Interventions that incorporated these factors were associated with effectiveness. Education about how to reduce future risk of Type 2 diabetes and using pedometers in interventions were not associated with intervention effectiveness. Other factors that future interventions should address consist of ‘putting others before yourself’; ‘putting off lifestyle change’; ‘lack of support from healthcare professionals’ and ‘being a healthy role model for families’. Conclusion: Combining the results of qualitative and quantitative studies can provide a nuanced understanding of the effectiveness of physical activity and lifestyle interventions. Keywords: Female, Diabetes, gestational, Diabetes mellitus, type 2, Exercise, Life style, Systematic review